Influence of Crop and Machine Parameters on the Performance of Okra Seed Extractor in Relation to Seed Quality - Kushwaha, H L; Srivastava, A P; Singh, Harpal (Journal of Agricultural Engineering, 2004)
Studies were conducted on the effect of different cylinder speeds (5. 6 and 7 m/s), concave clearances (7, 10 and 13 mm), moisture contents (12.3, 15.8 and 18.8 % d.b.) and type of extraction mechanism on seed quality. Three types of extractor drums, viz. square head bolted drum, rubberised and rasp-bar were used for seed extraction. Seed quality was evaluated for vigour index. dead seed, and germination at the constant feed rate of 70 kg/h. It was found that germination and vigour of seed decreased with increase in pod moisture content, The germination decreased with increase in cylinder speed, whereas quantity of dead seeds increased with cylinder speed. The concave clearance had only a small effect on germination. The best quality of seeds was found at 12.3 % moisture content (d.b.), 7 mm concave clearance and 5 m/s cylinder speed with the square head bolted drum. Based on these parameters a prototype of okra seed extractor was fabricated.